Model Kepemimpinan Pendidikan Kontingensial dan Situasional - Dedi Abu Samsudin; Eneng Muslihah; Shobri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Contingency is a leadership theory which argues that leadership effectiveness is determined by the suitability between leadership style and the environmental situation. This research was conducted to determine the contingency or situational educational leadership model. This research uses qualitative methods and the data collection technique used in this research is library research, namely the research object used by searching for and collecting data or literary information in the form of books, journals, magazines, reports, and the others. The research results show that there are at least three contingency leadership models, namely Fiedler's Contingency Model, Hersey and Blanchard's Contingency Model, and Robert J. House's Path Goal Theory Contingency Model.